Enhancing Arabic Learning: Innovative Snakes and Ladders Media Design - Ariyani, Mufarikha; Hikmah, Khizanatul (Universitas Muhammadiyah Sidoarjo, 2024)
This study employs an R&D approach, utilizing the ADDIE model, to investigate the development of snakes and ladders learning media for Arabic instruction. Initial analysis revealed the exclusive use of lecture-based teaching without supplementary media. Subsequently, the researcher designed a snakes and ladders learning module using the Canva application. The designed module underwent validation, with material experts providing unanimous approval and media experts offering constructive feedback. Implementation in a classroom setting garnered positive responses, with 97.50% and 92.50% from small- and large-scale assessments, respectively. Formative evaluation based on student feedback led to further refinements, including an enlargement to A3 size. Both qualitative and quantitative techniques were employed for data analysis, drawing on methods such as observation, interviews, and questionnaires. The study's results demonstrate the efficacy and potential of the innovative snakes and ladders media in enhancing Arabic language learning. Highlight: Utilizes R&D approach and ADDIE model for innovative Arabic learning media development. Validates the snakes and ladders module with expert input and implements it in a classroom setting. Demonstrates substantial improvement in Arabic language learning through formative evaluation and quantitative analysis. Keyword: R&D Approach, Arabic Language Learning, Snakes and Ladders Media, ADDIE Model, Innovative Pedagogy